Evidence of stress in β cells obtained with laser capture microdissection from pancreases of brain dead donors. Issue 2 (4th March 2017) - Ebrahimi, Aref; Jung, Min-Ho; Dreyfuss, Jonathan M.; Pan, Hui; Sgroi, Dennis; Bonner-Weir, Susan; Weir, Gordon C.
ABSTRACT: Isolated islets used for transplantation are known to be stressed, which can result from the circumstances of death, in particular brain death, the preservation of the pancreas with its warm and cold ischemia, from the trauma of the isolation process, and the complex events that occur during tissue culture. The current study focused upon the events that occur before the islet isolation procedure. Pancreases were obtained from brain dead donors (n = 7) with mean age 50 (11) and normal pancreatic tissue obtained at surgery done for pancreatic neoplasms (n = 7), mean age 69 (9). Frozen sections were subjected to laser capture microdissection (LCM) to obtain β-cell rich islet tissue, from which extracted RNA was analyzed with microarrays. Gene expression of the 2 groups was evaluated with differential expression analysis for genes and pathways. Marked changes were found in pathways concerned with endoplasmic reticulum stress with its unfolded protein response (UPR), apoptotic pathways and components of inflammation. In addition, there were changes in genes important for islet cell identity. These findings advance our understanding of why islets are stressed before transplantation, which may lead to strategies to reduce this stress and lead to better clinical outcomes.